Comparison Analysis of Modes Before and After Liquid Rocket Filling - Chen, Jiazhao; Wang, Xueren; Yue, Chunguo (International Journal of Mechanical and Electrical Engineering, 2024)
Taking the two-stage liquid rocket as an example, we use the ANSYS calculation software to consider the fluid-solid coupling after propellant filling, calculate the modes under the first and last two conditions of propellant filling, and obtain the first 20 natural frequency and vibration pattern of the liquid rocket, which provide reference for the safe use of the target range. The calculation results show that the natural frequency of the liquid rocket system decreases after propellant filling compared with that before filling, the modes of order 1 and 2 are low frequency vibration, the natural frequency amplitude changes significantly, while the natural frequency above order 6 is basically stable. Therefore, attention should be paid to eliminating the low frequency vibration source in the environment, and more attention should be given after filling. The 1 and 2 modes of the front and back liquid rockets are swinging, while the liquid rocket structure; the filling propellant will not affect the first 4 modes, but will only change the vibration plane.